The Value of Character Education in Tembang Dolanan Jawa and Its Implementation in The Cultural Art Learning Process - Lathifasari, Meisera Fika; Widodo, Widodo; Wadiyo, Wadiyo (Universitas Negeri Semarang, 2021)
One of the arts that is very full of Islamic nuance with the Kikim Tribe is the art of “Arakan” or